2004
DOI: 10.1002/maco.200303710
|View full text |Cite
|
Sign up to set email alerts
|

Influence of retrogression and reaging on microstructure, mechanical properties and susceptibility to stress corrosion cracking of an Al‐Zn‐Mg alloy

Abstract: The aim of the present work was to determine the influence of the retrogression and reaging (RRA) heat treatment on the correlation between microstructure, mechanical properties and susceptibility to stress corrosion cracking (SCC) of the AlZn5Mg1 alloy in dry air and sea water. The alloy received in the T6 temper was subjected to 9 different heat treatments, including retrogression at temperature 453 -513 K for 600 -3600 s, and reaging at temperature 363 K or 403 K for 16 h, 24 h or 48 h. The susceptibility t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Therefore, the RRA heat treatment provides for large grain boundary precipitates and coherent matrix precipitates which are responsible for enhanced SCC resistance and high strength, respectively, in 7075 aluminum alloy . It has also been indicated that RRA treatment in 7xxx series wrought alloys reduces the dislocation density, and therefore, reduces the susceptibility to SCC …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the RRA heat treatment provides for large grain boundary precipitates and coherent matrix precipitates which are responsible for enhanced SCC resistance and high strength, respectively, in 7075 aluminum alloy . It has also been indicated that RRA treatment in 7xxx series wrought alloys reduces the dislocation density, and therefore, reduces the susceptibility to SCC …”
Section: Introductionmentioning
confidence: 99%
“…[29] It has also been indicated that RRA treatment in 7xxx series wrought alloys reduces the dislocation density, and therefore, reduces the susceptibility to SCC. [24,30] To date, only a few reports, such as Refs. [8,31] , have investigated the effects of RRA heat treatment, which have been successful in 7xxx series aluminum alloys, on the corrosion behavior of B206.…”
Section: Introductionmentioning
confidence: 99%
“…Retrogression and reaging treatment can improve the stress corrosion behavior of the alloy while maintaining the mechanical resistance of the T6 temper [4][5][6][7][8][9][10][11][12]. The following are the steps involved in retrogression and reaging:  Specimens are placed in the muffle furnace for preaging.…”
Section: Heat Treatmentmentioning
confidence: 99%
“…The increase in the strength of the specimens are due to the formation of the more stable interphases like MgZn 2 [12][13][14] and also refinement of the grains at the said elevated temperature of retrogression for short interval of time.…”
Section: Data Meansmentioning
confidence: 99%
See 1 more Smart Citation